ChemInform Abstract: A Cesium Copper Vanadyl‐Diphosphate: Synthesis, Crystal Structure and Physical Properties. Issue 9 (March 2015) - Shvanskaya, Larisa; Yakubovich, Olga; Bychkov, Andrey; Shcherbakov, Vasiliy; Golovanov, Alexey; Zvereva, Elena; Volkova, Olga; Vasiliev, Alexander
Abstract Non‐centrosymmetric orthorhombic single crystals of Cs2Cu1.1(VO)1.9 (P2O7)2 are obtained by spontaneous crystallization from a melt containing CsH2PO4, CuO, and V2O5 in the molar ratio of 2:2:1 (Al2O3 crucible, 850 °C, 72 h).